Pemanfaatan Teknologi Virtual Reality Sebagai Sarana Pembelajaran Untuk Pengenalan Modul Platform Screen Door (PSD) Pada Stasiun Underground MRT Jakarta - Oscar Empe Rampengan; Arifianto, Teguh; Fathurrozi Winjaya (Sistem dan Teknik Transportasi Indonesia, 2025)
Technology media such as android smartphones can be used as an interesting and effective learning method. However, materials that require more skills or creativity, such as how the Platform Screen Door (PSD) components work, often encounter difficulties in learning. This study proposes the use of virtual reality-based applications as an alternative media to help learn PSD doors at the underground station MRT Jakarta. This application uses unity 3D and blender software. In the testing process, the author uses the black box testing method to ensure that each button and application feature functions properly. The testing involved cadets, educators, and education personnel at the Indonesian Railway Polytechnic Madiun. With the black box testing method, the results obtained were 100% successful with 30 trials. The test results show that this application is easy to use and effective in helping cadets learn maintenance, repairs, and PSD modules in an interesting way. Thus, virtual reality-based applications have great potential to increase learning effectiveness, especially in the context of complex material that requires in-depth understanding.